JENIS DAN TINGKAT PARASITASI PARASITOID TELUR PENGGEREK BATANG PADI PUTIH (Scirpophaga innotata WALKER) PADA PERTANAMAN PADI (Oryza sativa L.) DI DUA KETINGGIAN TEMPAT BERBEDA DI KABUPATEN SIGI - Mohammad Yunus, Hasriyanty, Edy Junaedi, (AGROTEKBIS, 2016)
This study aims to identify parasitoids species and determine the percentage of parasitism of white rice stem borer (S. innotata) on paddy rice cultivation at different altitudes (Below 200 m asl and higher than 500 masl). This research was conducted in December 2015 - March 2016, in the village of Vatunonju, Sigi Biromaru Subdistrict and Sejahtera Village, Palolo Subdistrict, Sigi District. Identification of parasitoids was conducted in the Plant Pest and Disease Laboratory, Faculty of Agriculture, University of Tadulako, Palu. The study sites was selected by purposive sampling method. Ten eggs group of white rice stem borer at each location were collected from paddy field at different altitude to identify their parasitoids and parasitism level. The study found three parasitoids species of white rice stem borer namely Tetrastichus sp., Telenomus sp., and Trichogramma sp.. Telenomus sp. was the dominant species at the low land (200 m asl) paddy fields while Tetrastichus sp. was dominating at the upland (>500 asl) paddy fields with parasitism level were 23.34% and 20.69% respecttively.